Distant Excitation of Rotating Surface Waves in Bodies with Cylindrical and Spherical Surface as Applied to Ultrasonic Control - A. R. Baev; A. V. Vorobei; A. L. Mayorov; M. V. Asadchaya; N. V. Delenkovsky (Приборы и методы измерений)
Increasing the efficiency of ultrasonic diagnostics and objects with curved surfaces, including cylindrical, spherical, etc., is an important scientific and technical task. The aim of the work was to develop a technique and experimentally investigate the excitation of surface rotating waves on cylindrical and spherical samples in contact with a metal substrate (support) using the proposed remote sounding method, where the substrate serves as an acoustic delay line for transmission-reception of signals between transducers and the object of investigation. The acoustic path of the suggested measuring scheme operating in shadow and echo modes has been analyzed and the dependences of the amplitude and velocity of the surface rotating waves excited in cylindrical steel and dural samples on their radius r, wave frequency ν and the number of revolutions n of the wave, while varying the angular wave number in the range p = 2πr/λ = 20–125 have been experimentally revealed. The quasi-linear growth of the wave attenuation coefficient from the sample diameter at frequencies ν = 1–5 MHz has been experimentally established. The growth of the distance travelled by the wave is accompanied by a drop in the amplitude of the wave according to a law close to the exponential law, reaching the greatest attenuation with a decrease in r. The change in the surface rotating waves velocity in the specified range of variation p did not exceed 1.5–2 %, increasing with decreasing sample radius and wave frequency. The obtained experimental data on the peculiarities of changes in the parameters of acoustic impulses during the passage of surface rotating waves through the crack and the model coatings of the specimens indicate the possibility of using the proposed method for the control of objects of the specified shape.